Sudden endotracheal tube block in a patient of Achalasia Cardia - Ajit Gupta; Kishor; Vinit Kumar Thakur; Arvind Kumar (Wolters Kluwer Medknow Publications, 2012)
Endotracheal tube block due to various mechanical causes such as mucous, blood clot, denture, and ampoules have been reported. A patient of achalasia cardia with chronic passive aspiration pneumonitis developed mucoid mass in the respiratory passage which dislodged during the surgical procedure. The episode occurred almost an hour after induction of anesthesia and the dislodged mucoid mass blocked the lumen of endotracheal tube, leading to hypoxia and impending cardiac arrest. However, the patient was salvaged by replacing the tube.